2017
DOI: 10.1111/jpn.12763
|View full text |Cite
|
Sign up to set email alerts
|

Comparative selective retention of particle size classes in the gastrointestinal tract of ponies and goats

Abstract: There is a discrepancy in the literature on potential digesta separation mechanisms in horses, with both a selective retention of fine and of large particles postulated in different publications. To assess the net effect of such mechanisms, we fed ponies on a hay-only diet a pulse dose of whole (unchopped) marked hay together with a solute marker, collected faeces on a regular basis, measured marker concentrations in whole faeces and in their large (2.0-16 mm), medium (0.5-1.0 mm) and small (0.063-0.25 mm) par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 62 publications
1
17
0
Order By: Relevance
“…For faecal samples obtained from the caecum of horses in the HS group, the fraction of particles that washed through the finest sieve (< 1 mm) constituted 69.50% of the digesta. This finding is particularly interesting if we consider that the CAE is one of the most common sites – together with the ileum and the large colon pelvic flexure (PF) – of gastrointestinal tract obstruction or faecal impaction [ 34 36 ]. Moreover, in the sternal flexure, the pelvic flexure, the right dorsal colon and the rectum, our results showed that the proportions of faecal particles retained by a 8 mm sieve and washed through the finest sieve (< 1 mm) were higher in horses fed the HS diet compared with those fed the HF diet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For faecal samples obtained from the caecum of horses in the HS group, the fraction of particles that washed through the finest sieve (< 1 mm) constituted 69.50% of the digesta. This finding is particularly interesting if we consider that the CAE is one of the most common sites – together with the ileum and the large colon pelvic flexure (PF) – of gastrointestinal tract obstruction or faecal impaction [ 34 36 ]. Moreover, in the sternal flexure, the pelvic flexure, the right dorsal colon and the rectum, our results showed that the proportions of faecal particles retained by a 8 mm sieve and washed through the finest sieve (< 1 mm) were higher in horses fed the HS diet compared with those fed the HF diet.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it is well known that high amounts of undigested starch are responsible for alterations or shifts in microbiome composition, which lead to a reduction in the activity of fibrolytic microorganisms [ 18 , 19 , 40 ] and, as a consequence, a reduction in the fermentation capacity of the fibre [ 40 , 41 ]. This aspect seems particularly important if we consider that the adequate digestion of fibre is believed to be crucial for reducing particle retention in the intestine, the occurrence of which increases the risk of large colon impaction [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The DMD differences compared with other studies can be attributed to differences in forage stage of maturity and inclusion levels in the diets. The observed DMD differences between the concentrate-based diet (MRG) and the forage dietary treatments (BG and CG) could be explained by small particle size of the concentrates and hence short retention period in the rumen (Hummel et al, 2018). However, concentrate DMD was very low (38.9%) compared with 55% reported for other maize bran-based diets (Omar et al, 1999;Safari et al, 2009), possibly due to inclusion of rice polish in that diet.…”
Section: Discussionmentioning
confidence: 84%
“…The difference between ruminants and nonruminants might stem from the fact that in ruminants, ingestive mastication is less systematic and consistent, and hence possibly less ‘fixed', than in nonruminants (Dittmann et al, 2017). The effect of intake on faecal particle size then stems from the fact that at high fill of the reticulorumen, larger particles may escape retention and re‐mastication (Hummel et al, 2018), rather than a reduction in rumination chewing efficiency itself (Findeisen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%